Bond strength between deformed steel reinforcement bar and steel fibre reinforced grout - Muhammad Fauzan Mahadzir, 1995-, author; Ahmad Baharuddin Abd. Rahman, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018